2019
DOI: 10.3727/096504019x15555408784978
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Mobility in Pancreatic Cancer Cells by Secreted S100A11 Through Activation of Surrounding Fibroblasts

Abstract: S100A11, a member of the S100 family of proteins, is actively secreted from pancreatic ductal adenocarcinoma (PDAC) cells. However, the role of the extracellular S100A11 in PDAC progression remains unclear. In the present study, we investigated the extracellular role of S100A11 in crosstalking between PDAC cells and surrounding fibroblasts in PDAC progression. An abundant S100A11 secreted from pancreatic cancer cells stimulated neighboring fibroblasts through receptor for advanced glycation end products (RAGE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…They therefore suggested that S100A11 be considered as an oncogenic factor (Sobolewski et al, 2020). In these cases, the upregulation of S100A11 significantly promotes the proliferation, migration, and tissue invasion of tumor cells by activating different signal pathways (Meng et al, 2019;Mitsui et al, 2019). A S100A11/ANXA2 complex has also been shown to be able to reseal the plasma membrane if it has become damaged due to the stress of metastatic tissue invasion (Jaiswal et al, 2014;Sobolewski et al, 2020).…”
Section: Cancersmentioning
confidence: 99%
“…They therefore suggested that S100A11 be considered as an oncogenic factor (Sobolewski et al, 2020). In these cases, the upregulation of S100A11 significantly promotes the proliferation, migration, and tissue invasion of tumor cells by activating different signal pathways (Meng et al, 2019;Mitsui et al, 2019). A S100A11/ANXA2 complex has also been shown to be able to reseal the plasma membrane if it has become damaged due to the stress of metastatic tissue invasion (Jaiswal et al, 2014;Sobolewski et al, 2020).…”
Section: Cancersmentioning
confidence: 99%
“…Several studies have confirmed that S100A11 was upregulated in cancers, such as pancreatic cancer, intrahepatic cholangiocarcinoma and ovarian cancer, involving in the progression of these cancers. 22 - 24 However, individual study suggested the downregulated expression of S100A11 in bladder cancer predicted the worse prognosis, indicating that S100A11 could perform both tumor suppression and promotion effects to influence the proliferation of cancer cells. 7 Whereas, the expression status and the potential role of S100A11 in different grades of glioma have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the TPL2-ERK1/2 signaling pathway can induce metastasis by activating the transcription factor ETS translocation variant 4 (ETV4) that induces the expression of matrix metalloproteinase-25 (MMP25) 64 . MMP25 is a membrane-anchored matrix metalloproteinase that plays a vital role in the onset of tumor dissemination and the induction of the COX2/PGE2 signaling pathway 64 , 65 . Clinical samples from cancer patients further confirm the connection between TPL2 and metastasis.…”
Section: Tpl2 and Tumorigenesismentioning
confidence: 99%
“…The tumor microenvironment in mature tumors is characterized by a heterogeneous group of activated fibroblasts known as cancer-associated fibroblasts (CAFs) that interact with cancer cells and other stromal cells to propagate tumor growth and disease progression 44 , 87 . The TPL2 activity is implicated in CAFs activation, where it sustains the pro-inflammatory transcriptional signature that contributes to tumor progression and metastasis 25 , 65 . Despite its essential role in the production of inflammatory factors, TPL2 loss in CAFs was reported to promote NF-κB activation, inflammation and tumorigenesis 88 .…”
Section: Tpl2 and Tumor Immunitymentioning
confidence: 99%